2019
DOI: 10.1007/s10068-019-00582-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sucrose on rheological properties of xanthan gum-locust bean gum mixtures

Abstract: The effect of sucrose (0, 10, 20, 30, and 40%) on flow and dynamic rheological properties of xanthan gum (XG) mixed with locust bean gum (LBG) at different mixing ratios (100/0, 75/25, 50/50, and 0/100) were evaluated. The addition of sucrose significantly changed the flow behavior index (n), consistency index (K), storage modulus (G 0), and loss modulus (G 00) of XG, LBG, and XG-LBG mixtures. When XG and LBG were mixed, there was a synergistic effect on K and G 0 values, and 50XG/ 50LBG mixture exhibited stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…It was also observed that G' values of the LBG and XSG solutions were much lower than the mixtures due to the synergistic interaction resulting in a solution with higher viscosity. In a study which was observing the effect of sucrose to synergistic effect of XSG/LBG mixtures, it has been stated that the mixing ratio of the gums and sucrose ratio has an impact on the synergistic interaction between XSG and LBG mixtures since there was a competition between gums and sucrose (Jo & Yoo, 2019). G' values were higher than G ″ values in all mixed solutions; however, it was the vice versa for LBG and XSG solutions.…”
Section: Resultsmentioning
confidence: 99%
“…It was also observed that G' values of the LBG and XSG solutions were much lower than the mixtures due to the synergistic interaction resulting in a solution with higher viscosity. In a study which was observing the effect of sucrose to synergistic effect of XSG/LBG mixtures, it has been stated that the mixing ratio of the gums and sucrose ratio has an impact on the synergistic interaction between XSG and LBG mixtures since there was a competition between gums and sucrose (Jo & Yoo, 2019). G' values were higher than G ″ values in all mixed solutions; however, it was the vice versa for LBG and XSG solutions.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in viscosity as xanthan concentration increases can be attributed to its semirigid conformation and shear thinning behavior. The shear thinning behavior of xanthan solutions was found to increase with sucrose concentration (Jo & Yoo, 2019). In the case of binary blends, the viscosity was intermediary between the viscosities of individual hydrocolloids.…”
Section: Resultsmentioning
confidence: 99%
“…The average viscosity value at a shear rate of 10 s À1 after running the rheological test for 1 min is shown in Figure 1 for the pureed carrot matrices with and without saliva. (Jo & Yoo, 2019). In the case of binary blends, the viscosity was intermediary between the viscosities of individual hydrocolloids.…”
Section: Viscosity Measurementsmentioning
confidence: 99%
“…LBG show slightly soluble in cold water and needs to be heated to achieve maximum viscosity. Hydrocolloid has the ability to form viscous solutions at low concentrations and may produce coatings and films with high density, characterized by good mechanical and water vapor barrier properties (Aloui et al, 2014; Jo & Yoo, 2019; Mikkonen et al, 2010). Locust bean gum (Carob) is used like gum tragacanth as a thickener, stabilizer, gelling agent, emulsifier or carrier.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be a cocoa substitute due to its unique organoleptic qualities, low fat content, hypoallergenic and no caffeine. The addition of locust bean gum to baked goods improves their color, texture, taste and aroma, facilitates cutting the dough, prevents caking, and extends the freshness of products by binding more water (Brassesco et al, 2021; Jo & Yoo, 2019). Carob flour dissolves well in milk, salt and sugar solutions, in water at a temperature above 80°C it forms highly viscous solutions stable in the pH range of 4.4–10, and undergoes hydrolysis in the environment with pH <3.…”
Section: Introductionmentioning
confidence: 99%